Pola Makan 3J, Aktivitas Fisik, dan Glukosa Darah Sewaktu Penderita Diabetes Melitus Tipe 2 Usia Produktif di Prolanis Puskesmas Ajung - Kusmita, indriyani; Ningtyias, Farida Wahyu; hartanti, ragil ismi (Jurnal Kesehatan, 2023)
A number of Diabetes mellitus type 2 among productive age group increased from 6.9% to 8.5% between 2013 and 2018. To prevent them from severe complication, they should apply diet pattern which is right in quantity, type, and meal plan (3J principles), and reglukosar physical activity. Therefore, this paper aims to describe both variables based on blood glucose levels of working age patients with DM type 2 in Prolanis of Ajung Primary Health Care, Ajung, Jember. Based on descriptive method, the former data was collected by Food Frequency Questionnaire (FFQ) and 2x24-hour recall form, while the latter was measured by Global Physical Activity Questionnaire (GPAQ). At the same time, we also took a random blood glucose test throughout a couple of visits to calculate the average. The results revealed that participants were dominated by females, high-school graduates and housewives. Furthermore, 72.7% of participants having poor glucose levels in which all of those tend to have poor diet of 3J. The result was contributed by participaants who has been eating without a proper food quantity and meal plan. In fact, the majority of participants who were doing moderate physical activities (59.1%) also categorized as patients with poor blood glucose level (50%). Concluded, most participatns did not pratice the diet  pattern of 3J in their daily diet although they had high blood glucose level. This paper, thus, encourages further research to focus on statistical analysis between diet pattern, physical activity, and blood glocose among productive group.